A política pública do estado de Mato Grosso para a Educação de Jovens e Adultos e o trabalho dos professores formadores da EJA - Santos, Sávio Antunes dos (2013)
This work is the result of research masters in education in the Graduate Program in Education of the Federal University of Mato Grosso - PPGEDU / UFMT / Rondonópolis-MT, in the search line Teacher Education and Public Policy. The study is in the continuing education of teachers talking on the assumption Freire's inconclusiveness, in constant pursuit of being more in its historical time, because if history is not finished, so education is subject to possible man or woman, young or adult. Therefore I reflect the formation of the subject trainer teacher of Youth and Adult Education (EJA), an unfinished being that handles incompleteness of teachers working in schools in EJA. I elect the following research problem: how teacher educators to rethink public policy of the Mato Grosso State to the EJA in fostering the formation of school teachers? To do this analysis documents, specifically the Policy Document for Public EJA, and disposal also interviews of four subjects / teacher trainers EJA from four different Cefapros. In the analysis I turn to dialectics, as I believe to be an important tool dialectic and expensive for the discussion of the data, understanding that education can not be explained by itself, thus requiring vision and understanding of other contexts that directly or indirectly influence or define education. I have as the theoretical basis to support the conceptual discussions of fundamentals and interpretive understanding of the data collected for research, Freire (2005, 2008a / b / 2009a / b /, 2011), Arendt (2010, 2011); Nóvoa (2009), Arroyo (2006, 2007); Imbernon (2009, 2010), Soares (2007, 2011). This option for dialogue with Freire begins after the research process of this dissertation and the path taken during the construction of the theoretical framework meant to broaden my understanding of his teachings and trust in him, to think of education in favor of transformation of reality and freedom of men and women so that the ideas by Freire and substance directs my thoughts and ponderings throughout the work. The Education of Young and Adult is marked by its denial for centuries and its recent inclusion in the official scenario of Brazilian education. It sets both in the field of popular education as the education systems, so the EJA is located at a point of tension. In this scenario continuing education shows itself as a useful and necessary way in understanding the specifics of the challenge presented in this mode. Soon the teacher educators are key players of EJA in mediating public policy EJA, considering that the objectivity of the policies are diluted in the subjectivity of the relationships, so in fostering the training of school teachers teachers trainers can make choices in relation to the world and for the world, not exempting the liability for these educators who are also young adults and unfinished